2003
DOI: 10.1128/aac.47.12.3825-3830.2003
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Resistance in Campylobacterjejuni and Campylobacter coli Strains Isolated in 1991and 2001-2002 from Poultry and Humans in Berlin,Germany

Abstract: The susceptibilities of 430 Campylobacter jejuni strains and 79 C. coli strains to six antimicrobial agents were tested and analyzed. The two sets of strains originated from retail market chicken and turkey samples and from humans, respectively, in Berlin, Germany. Two groups of isolates, one dating from 1991 and the other dating from 2001-2002, were tested. Of the Campylobacter sp. isolates recovered from humans in 2001-2002, 45.1% were resistant to ciprofloxacin, 37.8% were resistant to tetracycline, 12.8% w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
59
1
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(69 citation statements)
references
References 25 publications
8
59
1
1
Order By: Relevance
“…In this study, antimicrobial resistance of C. coli isolates to EM from pigs (P<0.05, chi-square test with Yete's correction for continuity) was significantly higher than that from beef cattle. Luber et al [11] suggested that pigs were a likely source for EM-resistant C. coli infections in humans. Harada et al [5] reported that EM resistant C. coli isolates increased slightly but constantly from 1999 to 2004 and suggested that the dynamics of EM resistance in porcine C. coli isolates should be noticed for risk management of antimicrobial resistance in Campylobacter.…”
mentioning
confidence: 99%
“…In this study, antimicrobial resistance of C. coli isolates to EM from pigs (P<0.05, chi-square test with Yete's correction for continuity) was significantly higher than that from beef cattle. Luber et al [11] suggested that pigs were a likely source for EM-resistant C. coli infections in humans. Harada et al [5] reported that EM resistant C. coli isolates increased slightly but constantly from 1999 to 2004 and suggested that the dynamics of EM resistance in porcine C. coli isolates should be noticed for risk management of antimicrobial resistance in Campylobacter.…”
mentioning
confidence: 99%
“…In 1998, 3% C. jejuni/coli resistant strains were reported in Canada, but the percentage rose to 12% in 2001 (Gaudreau and Michaud, 2003). In Germany, 7.1 and 29.4% C. coli resistant to erythromycin were reported in 1991 and 2001, respectively (Luber et al, 2003). Besides, a rising trend of resistance to erythromycin was reported in Northern Ireland, from 0.6% in 1996 to 4.2% in 2000 (Moore et al, 2001).…”
Section: Discussionmentioning
confidence: 98%
“…isolated from humans has become allarming (Bywater et al, 2004;Cardinale et al, 2002). Emergence of the resistant strains coincided with the beginning of macrolides use, for the most part thylosine, in veterinary medicine, mainly in swine farming ( Aarestrup and Engberg, 2001;Luber et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…It is lowest in Canada (12%) and Germany (0%) (C. jejuni) (Gibreel et al, 2005;Gaudreau and Gilbert, 2003;Luber et al, 2003) and highest in Taiwan (C. coli) 50% (Li et al, 1998) and Nigeria 79.8% . However a study on macrolide resistance in C. jejuni in Sweden showed stable pattern (Engberg et al, 2001;Osterlund et al, 2003).…”
Section: Discussionmentioning
confidence: 99%